ANALISIS MINAT BEKERJA DAN STUDI LANJUT SISWA SMK DI KOTA SURAKARTA DITINJAU DARI AKADEMIK DAN EKONOMI - Zaena Hapsari; Suharno Suharno; Ranto Ranto (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
The purpose of this research is to : 1) influence academic and economy to interest enter world industri SMK students throughout Surakarta and influence academic and economist to interest studies carry on SMK students in Surakarta. Method research used in study this that is with method study quantitative descriptive . Population used by 452 students with taking sampel by Simple Random Sampel as many as 213 students . The data collected used questionnaire questionnaire . Technique analysis used that is technique analysis multiple linear regression . Results study show that : 1) there is significant influence between academic variabels to interest enter industrial world with sig value 0.023 < 0.05. 2) there significant influence between economic variabels to interest enter industrial world with sig value 0.00<0.05. 3) there significant influence  between academic variabels to interest studies carry on with score significance 0.046 < 0.05. 4) no there is significant influence between economic variabels to interest studies carry on with score significance 0.174 > 0.05.